ChemInform Abstract: A Highly Active Catalytic System for Suzuki—Miyaura Cross‐Coupling Reactions of Aryl and Heteroaryl Chlorides in Water. Issue 19 (18th April 2013) - Mao, Shu‐Lan; Sun, Yue; Yu, Guang‐Ao; Zhao, Cui; Han, Zhi‐Jun; Yuan, Jia; Zhu, Xiaolei; Yang, Qihua; Liu, Sheng‐Hua
Abstract A wide range of aromatic and heteroaromatic chlorides and some bromides, including hindered, activated and deactivated ones, are applied in the Suzuki—Miyaura cross‐coupling reaction in water to afford the products with moderate to high yields.